Additive Manufacturing of PE/fluorouracil/progesterone intrauterine device for endometrial and ovarian cancer treatments. (October 2018) - Salmoria, G.V.; Vieira, F.E.; Muenz, E.A.; Gindri, I.M.; Marques, M.S.; Kanis, L.A.
Abstract: Progesterone and fluorouracil loaded-intrauterine drug delivery systems were prepared using selective laser sintering (SLS). PE/FU/PG IUDs had small particles of fluorouracil spread over the IUD surface and progesterone was dispersed within the porous PE matrix. The existence of additional peaks related to the fluorouracil and progesterone confirm their presence at 10% concentration by both DSC and FTIR. The PE/FU/PG IUDs prepared using higher laser power (5 W) had the highest flexural modulus, probably due to better PE particle coalescence. The PE/FU/PG IUDs initially showed rapid drug release due to the hydrophilic characteristics of fluorouracil. This is a desirable profile as it provides a high initial concentration of the drug locally to the cancer cells following implantation. The slow and controlled release of the progesterone presented by PE/FU/PG IUDs is interesting for sustained levels of the hormone therapy agent in the region of the tumor with the potential to enhance the cancer treatment. Highlights: Progesterone and fluorouracil loaded-intrauterine drug delivery systems were prepared using selective laser sintering (SLS). Physicochemical, mechanical and drug release properties were determined. Higher laser powered yielded devices with better mechanical properties. Drug release profile demonstrate influence of drug hydrophilicity on elution rate. The IUD prepared in this work has great potential for future applications in cancer treatment.